1989
DOI: 10.1111/j.1540-6288.1989.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

The Investment Performance of Common Stocks in Relation to Their Price–Earnings Ratios: An Update of the Basu Study

Abstract: In this paper, the relationship between the investment performances of equity securities and their price–earnings ratios is examined using an approach similar to the one employed by Basu in a 1977 paper. From the tests, we conclude that, from 1979 through 1984, there were some moderate excess rates of return earned by selecting stocks based on their price–earnings ratios but that these excess rates were not obtained from investing in low price–earnings stocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 9 publications
1
24
1
Order By: Relevance
“…Jones (1987) and Johnson et al (1989) are among those who find the opposite results in their studies. Jones found that stocks with low P/E ratio produced significantly lower risk adjusted rates of return as compared to those following the Standard and Poor 500 or other investment strategies.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Jones (1987) and Johnson et al (1989) are among those who find the opposite results in their studies. Jones found that stocks with low P/E ratio produced significantly lower risk adjusted rates of return as compared to those following the Standard and Poor 500 or other investment strategies.…”
mentioning
confidence: 92%
“…This study, by repeating partially Johnson et al (1989) procedures, was trying to confirm the low P/E effect hypothesis in Indonesian market. The study involved 267 stocks listed in Jakarta Stock Exchange in the sample frame and selected the period of 1994-2000 as the focus of analysis.…”
Section: From Practical Point Of View Price-earnings (P/e) Ratio Is mentioning
confidence: 99%
See 3 more Smart Citations